Fibrous antigorite in Mount Reventino area of central Calabria - Campopiano, Antonella; Bruno, Maria Rosaria; Olori, Angelo; Angelosanto, Federica; Iannò, Antonino; Casciardi, Stefano; Spadafora, Alessandra (Journal of Mediterranean Earth Sciences, 2018)
<span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Naturally Occurring Asbestos (NOA) can form in several types of geologic settings depending on the rock types and geologic history of an area. Calabria region has many settings that are favourable for the presence of NOA because of the variety of older metamorphic and igneous rocks and by the multiple episodes of deformation that many of these rocks have undergone. In Calabria NOA are mainly concentrated in the ophiolitic sequences belonging to the Gimigliano-Mount Reventino Unit in the <span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">southern part of the <span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Sila <span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">massif <span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">and along the Coastal Chain. The amphibole-group asbestos, in particular tremolite, is the most common type of asbestos found in Calabria. However, serpentine minerals were found, especially in Mount Reventino surroundings. T<span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: TT10A1Co00; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: TT10A1Co00;" lang="EN-GB">he purpose of this study was to report the presence <span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Plantin-BoldA; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: Plantin-BoldA;" lang="EN-GB">of asbestiform antigorite, one of the natural mineral fibers of the serpentine group, very abundant and commonly found associated with asbestos chrysotile in <span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Plantin-BoldA; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">metabasites and serpentinites outcrops in the <span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Mount Reventino area<span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">. The set of the different analytical techniques: optical microscopy, scanning and transmission electron microscopy combined with energy dispersive spectroscopy and Fourier transform infrared spectroscopy analyses allowed its complete characterization.<span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US"> Antigorite showed fibers with a length-to-width ratio around 20 and more. The toxicological studies indicate a <span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-GB">carcinogenic potential more closely aligned to that amphibole asbestos. <span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">In absence of epidemiologic studies, <span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">further research about the degree of asbestiform antigorite hazard are necessary. A<span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">ctions should be taken to avoid or diminish a possible risk using the same prevention measures as for asbestos fibers,<span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> although fibrous antigorite is not recognized in most asbestos regulation.